A dielectric breakdown model for an electrode along an interface between two piezoelectric materials. (1st February 2020) - Loboda, V.; Sheveleva, A.; Chapelle, F.; Lapusta, Y.
Highlights: An electrically charged interface electrode in a piezoelectric bimaterial is considered. To remove the obtained singularities the dielectric breakdown model is applied. An exact analytical analysis of this model is carried out. The influence of the electrode charge and material heterogeneity is studied. Good agreement with finite element solution of a similar problem is revealed. Abstract: A plane strain problem for an interface electrically charged thin electrode in a bimaterial piezoelectric space is considered. Remote in-plane mechanical loading and an electrical field parallel to the electrode faces are applied. The known solution of this problem demonstrates the electromechanical field singularities at the electrode tips. To remove these singularities the dielectric breakdown model is applied. Using the presentations of electromechanical quantities via sectional analytic functions the Riemann-Hilbert problem with discontinuous right side is formulated and solved exactly. The dielectric breakdown zone lengths are found from the electric field finiteness at the end points of these zones. It is shown that this length depends on the external electric field and the electrode net charge. The variations of electromechanical characteristics along the electrode and its continuation are presented in graphical form. Particular cases of an uncharged electrode and homogeneous material are considered and compared with previously obtained results. A verification of the obtained solutions by means of the ABAQUS code is carried out and good agreement of analytical and numerical results is revealed.